Peculiarities of multidrug-resistant tuberculosis on the background of idiopathic pulmonary fibrosis (a clinical case report) - O. M. Raznatovska; M. O. Shalmina; A. V. Fedorets; O. S. Shalmin; M. S. Potapenko (Zaporožskij Medicinskij Žurnal)
Objective – familiarization of practitioners with the peculiarities of pulmonary multi-drug resistant tuberculosis (MDRT) in a patient with idiopathic pulmonary fibrosis (IPF) resulted from a long exposure to environmental factors at the workplace.